Max Yergan : Race Man, Internationalist, Cold Warrior. - Anthony, David Henry, 1952- (NYU Press, 2005)
In his long and fascinating life, black activist and intellectual Max Yergan (1892-1975) traveled on more ground--both literally and figuratively--than any of his impressive contemporaries, which included Adam Clayton Powell, Paul Robeson, W.E.B. Du Bois, and A. Phillip Randolph. Yergan rose through the ranks of the "colored" work department of the YMCA, and was among the first black YMCA missionaries in South Africa. His exposure to the brutality of colonial white rule in South Africa caused him to veer away from mainstream, liberal civil rights organizations, and, by the mid-1930s, i.